Overview of Service Quality on Commitment Patient Revisit During the Covid-19 Pandemic at the Dental and Oral Polyclinic - Alif Chandra Aryono; P.A. Kodrat Pramudho (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Puri Husadatama Hospital is the only private hospital in Mesuji Regency, to provide promotive, preventive, curative, and rehabilitative health services, one of which is through the dental and oral polyclinic. Providing quality services to patients is one way to increase repeat visits to the hospital's polyclinic. The data shows that 194 people visited the dental and oral polyclinic in 2020, and 509 people in 2021, which shows an increase in patient visits of 262.4%. This study aims to describe the dimensions of service quality on a commitment to repeat patient visits to dental and oral services at the dental and oral polyclinic of Puri Husadatama Hospital during the COVID-19 pandemic in 2021. This type of research is a descriptive study with a cross-sectional approach. Samples were selected randomly from 509 patients and 105 respondents were recruited. Due to the Covid-19 pandemic, data collection was carried out using a questionnaire with a google form. Descriptive data processing and analysis. The research was carried out in December 2021. The results showed that patients with repeat visits > 1 time 103 people (98.1%), tangible category good 84 people (80,0%), empathy good category 101 people (96.0%), reliability good category 103 people (98,0%), responsiveness in good category 101 people (96,0%), assurance in good category 103 people (98,0%). The conclusion is that patients who visit again have high confidence in the quality of the dental and oral-service polyclinic (94.0%), while from the 5 (five) quality dimensions, respondents gave a high score. Recommendations are put forward that the quality of services at the dental and oral polyclinic is maintained, which is supported by the commitment of the leaders of the polyclinic and Puri Husadatama hospital.